Continuous evaluation of the literacy and learning media of students with visual impairment - Pandurevikj, R.; Dimitrova Radojichikj, Daniela (Faculty of Philosophy, Skopje, 2012)
The procedure for determining an adequate literacy and learning method among students with visual impairments consists two components: an initial choice of mode of literacy, to be conducted during the early childhood and continuing evaluation of the literacy and learning method, which is carried out over students who have already been involved in the educational process for a certain period and with whom a mediums for literacy and learning has already been determined. PURPOSE: The purpose of this research is to conduct a re-evaluation of the initial decision regarding the choice of media through which education is conducted among students with visual impairment. The speed of reading is substantially below the predicted minimum level both with students who read Braille and with students who read regular print. It should be mentioned that only 3 respondents out of 15 Braille readers were cooperative in this part of the research, so they obtained results regarding them should not be taken as reliable ones. 100% of the respondents who are educated using the Braille alphabet independently read unfamiliar formal and also familiar educational material. Among the students who use regular print, 62.5% read independently and the other 37.5% need additional instruction. 45.5% of them successfully completed their school assignments using their initially chosen medium for literacy and learning, but only 18.2% of them do it in an acceptable time period. 53.6% of respondents know how to use available resources and facilities that exist within the school, while the other 46, 4% need additional training and instructions. Continuous evaluation should be implemented consistently throughout the schooling of the child, or at least once a year, for a relevant "justification" for any change, addition or selection of another sensory channel for learning and literacy of the child, as a result of certain changes in visual functioning of the child or due to changes in the terms of their education.
Keywords: continuous evaluation, literacy, reading, students with visual impairment